2021
DOI: 10.3390/ijerph19010008
|View full text |Cite
|
Sign up to set email alerts
|

Poor School-Related Well-Being among Adolescents with Disabilities or ADHD

Abstract: Poor school-related well-being may influence adolescents’ school performance and lifestyle. Adolescents having disabilities or ADHD are in a vulnerable situation for having poor school-related well-being, compared to adolescents not having disabilities. We used cross-sectional data from a school-based survey among 15–18-year-olds (N = 4071) in Sörmland, Sweden, to analyse the association between poor school-related well-being and disabilities or ADHD. The analyses were carried out by logistic regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In addition to the possible positive effects mentioned above, it should be considered important to generate further knowledge concerning whether the positive effects reported for children with mental health problems are truly positive effects of distance learning or whether such effects are better explained as an absence of the negative effects of regular schooling. A considerable body of research conducted before the pandemic has shown that children with ADHD and/or ASD do not only perform worse academically, but that they, more often than controls, experience school-related problems such as higher levels of bullying [e.g., 63 , 64 ], school anxiety [ 49 ], lower school well-being [ 65 ], more peer problems [e.g., 66 , 67 ], as well as lower social involvement in the classroom [e.g., 68 ]. In addition, studies conducted during the COVID-19 pandemic have revealed a decrease in, for example, bullying [e.g., 69 ] and body-weight concerns [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the possible positive effects mentioned above, it should be considered important to generate further knowledge concerning whether the positive effects reported for children with mental health problems are truly positive effects of distance learning or whether such effects are better explained as an absence of the negative effects of regular schooling. A considerable body of research conducted before the pandemic has shown that children with ADHD and/or ASD do not only perform worse academically, but that they, more often than controls, experience school-related problems such as higher levels of bullying [e.g., 63 , 64 ], school anxiety [ 49 ], lower school well-being [ 65 ], more peer problems [e.g., 66 , 67 ], as well as lower social involvement in the classroom [e.g., 68 ]. In addition, studies conducted during the COVID-19 pandemic have revealed a decrease in, for example, bullying [e.g., 69 ] and body-weight concerns [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with mild to borderline intellectual disability ranged from 0.0% to 49.8% for tobacco use in a literature review. 24 Tiikkaja and Tindberg 25 found using tobacco were more frequent among adolescents in the disability group compared to peers with no disability, and the associations were even stronger adolescents with ADHD. Overall, McMillen et al 26 found that students with disabilities were at significantly higher risk for cigarette smoking, using alcohol, being overweight, feeling sad or hopeless, feeling stressed, feeling alone, and considering suicide.…”
Section: Methodsmentioning
confidence: 98%
“…One study (Tiikkaja & Tindberg, 2021) analyses the relationship between poor school-related well-being and disabilities or ADHD among adolescents aged 15-18 in Sweden. Young people with disabilities or ADHD reported that their disability had a negative impact on their schooling and compared to peers without disabilities, those with disabilities have an increased risk of poor school-related well-being.…”
Section: Well-being At Schoolmentioning
confidence: 99%